Reckoning : an FBI thriller - Coulter, Catherine (2022)
"Agents Savich and Sherlock are back in the latest installment in Catherine Coulter's #1 New York Times bestselling FBI Thriller series, and this time both are enlisted to help women with traumatic pasts who are in mortal danger"--